A systematic review of feather mites of the pterodectes generic complex (acari: Proctophyllodidae: Pterodectinae) with redescriptions of species described by vladimír cerný - Valim, M. P. (2010)
Five species of feather mites originally described in the genus Pterodectes by Vladimir černý (1974) are redescribed: Pterodectes havliki, P. maculatus , P. reticulatus, P. storkani, P. thraupicola and P. troglodytis. The formerly unknown males of P. thraupicola and P. reticulatus and the female of P. maculatus are described for the first time. A synopsis of known species of the Pterodectes generic complex is presented, and species content of the genus Pterodectes is revised. Fifteen species previously included in this genus are transferred to the new genus Amerodectes gen. n.: Amerodectes atyeoi (OConnor et al., 2005) comb. n., A. bilineatus (Berla, 1958) comb. n., A. geothlypis (Berla, 1973) comb. n., A. gracilis (Trouessart, 1885) comb. n., A. maculatus comb. n., A. molothrus (Mironov, 2008) comb. n., A. nordestensis (Berla, 1958) comb. n., A. paroariae (Mironov, 2008) comb. n., A. pitangi (Mironov, 2008) comb. n., A. tangarae (Mironov, 2008) comb. n., A. turdinus (Berla, 1959) comb. n., A. sialiarum (Stoll, 1893) comb. n., A. storkani (černý, 1974) comb. n., A. thraupicola (cčerný, 1974) comb. n., and A. troglodytis (černý, 1974) comb. n. Five species are transferred to the genus Tyrannidectes Mironov, 2008: Tyrannidectes amaurochalinus (Hernandes et Valim, 2006) comb. n., T. banksi (Valim et Hernandes, 2008) comb. n., T. crassus (Trouessart, 1885) comb. n., T. fissuratus (Hernandes et Valim, 2005) comb. n., and T. reticulatus (Cerný, 1974) comb. n.; and one species is moved to the genus Metapterodectes Mironov, 2008: Metapterodectes muticus (Banks, 1909) comb. n. The genus Pterodectes remains monotypic, with the type species P. rutilus Robin, 1877. © Acarina 2010.